ORAL MANIFESTATIONS OF AMYLOIDOSIS AS AN EARLY INDICATOR OF THE DISEASE - A LITERATURE REVIEW - Kinga Popielarska,; Borowski, Michał; Anna Maria Zakrzewska,; Julia Aleksandra Leśniak,; Natalia Maria Leśniak,; Julia Agnieszka Michalak,; Klaudia Elżbieta Niwińśka,; Klaudia Martyna Patrzykąt,; Aleksander Midera,; Monika Augustyn, (International Journal of Innovative Technologies in Social Science, 2026)
Introduction and Purpose: Amyloidosis is a rare group of diseases characterized by the irreversible extracellular deposition of insoluble amyloid fibrils in various organs and tissues. Treatment should begin as early as possible, immediately following diagnosis. Therefore, clinicians should be aware of the disease’s characteristic features, including those visible in the oral cavity- which will be the focus of this article. While systemic manifestations are often emphasized, changes in the oral cavity can serve as early- and sometimes the first- indicators of the disease.The aim of this article is to present the most relevant and recent scientific reports from the past ten years regarding oral manifestations of amyloidosis, highlight their diagnostic value, and emphasize the role of the dental professionals in the multidisciplinary approach to early detection and patient care.Description of the State of Knowledge: Recent literature highlights a broad range of oral manifestations in amyloidosis, including macroglossia, nodular lesions, hemorrhagic changes, and chronic ulcers- some of which may appear without systemic symptoms. Histopathological biopsy with Congo red staining remains the gold standard for confirming amyloid deposits. Case reports increasingly show that oral findings can prompt systemic evaluation, leading to earlier diagnosis and management. This underscores the importance of dental professionals in recognizing subtle signs and initiating appropriate referrals.Conclusions: Oral signs of amyloidosis can be the first clue to a systemic disease. Recognizing the type and location of lesions helps assess whether the disease is localized or systemic. Early diagnosis may improve outcomes- and in some cases, even save the patient’s life.